PERAN AKUNTANSI SEKTOR PUBLIK DALAM PERENCANAAN ANGGARAN PADA KINERJA KEUANGAN DAERAH KOTA SIDOARJO - Hastuti, Nova Asteria (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this study examined influence to know the role of accounting public sector in the financial planning budget at Sidoarjo. Where the role of accounting public sector which the most major is as a planning tool. While goverrment financial accounting describing about financial condition of an organization that include on revenues state and expenditures. The result of the study indicated that?s financial planning budget at Sidoarjo effective. Keywords: Accounting Public Sector, Government Financial Accounting.